Waste Composite Sensor Designed by Cellulose and Activated Carbon as Ethylene Absorber. (30th June 2016) - Ummartyotin, S.; Pechyen, C.
Abstract : Activated carbon was successfully derived from scrap tile waste from thermochemical conversion. Chemical and physical modifications were therefore employed to modify the specific surface area and porosity of activated carbon. Cellulose was successfully extracted from palm front. Designation of waste composite was prepared by cellulose and activated carbon. Less than 30 wt% of activated carbon was integrated into cellulose sheet matrix. It was important to note that there is no change in mechanical and morphological properties. Small amount of activated carbon was well dispersed. In order to investigate the feasibility of composite as active packaging, oxygen permeation rate and ethylene gas adsorption ability were preliminary investigated.